Numerical Investigation of Fluid Flow and Heat Transfer Inside a 2D Enclosure with Three Hot Obstacles on the Ramp under the Influence of a Magnetic Field - Keshtkar, M. M.; Ghazanfari, M. (Engineering, Technology & Applied Science Research, 2017)
This paper focuses on solving the fluid flow and heat transfer equations inside a two-dimensional square enclosure containing three hot obstacles affected by gravity and magnetic force placed on a ramp using Boltzmann method (LBM) applying multiple relaxation times (MRT). Although, the Lattice Boltzmann with MRT is a complex technique, it is a relatively new, stable, fast and high-accurate one. The main objective of this research was to numerically model the fluid flow and ultimately obtaining the velocity field, flow and temperature contour lines inside a two-dimensional enclosure. The results and their comparisons for different types of heat transfer revealed that free or forced heat transfer has a considerable impact on the heat transfer and stream lines. This can be controlled by modifying the Richardson number. It is revealed that changing the intensity of the magnetic field (Hartman number) has an appreciable effect on the heat transfer.